Sporadic Creutzfeldt‐Jakob disease: A case report and review of literature - Rajeev Ojha (Clinical Case Reports, 2020)
Abstract Creutzfeldt‐Jakob Disease is a rare neurodegenerative disease and earlier diagnosis is usually difficult. Combining clinical features with electroencephalogram, laboratory parameters, and neuroimaging findings will facilitate the diagnosis.